2020
DOI: 10.1159/000513236
|View full text |Cite
|
Sign up to set email alerts
|

The Unique Role of 11-Oxygenated C19 Steroids in Both Premature Adrenarche and Premature Pubarche

Abstract: <b><i>Introduction:</i></b> Recent studies have shown 11-oxygenated androgens (11oAs) are the dominant androgens in premature adrenarche (PA). Our objective was to compare 11oAs and conventional androgens in a well-defined cohort of children with PA or premature pubarche (PP) and correlate these androgens with metabolic markers. <b><i>Methods:</i></b> A prospective cross-sectional study was conducted at a university hospital. Fasting early morning serum steroids … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…Exclusion criteria were a history of chronic illness or other known endocrinopathies, evidence of adrenal enzyme defect, elevated inflammatory marker (C-reactive protein), history of hormone exposure, chronic glucocorticoid use, psychostimulant use, use of antibiotics in the prior 3 months, or use of probiotics in the last 1 month. The case group was previously subdivided into PA and PP subgroups based on elevation of adrenal androgen serum DHEAS in a prior study 4 ; however, as described in our publication, there did not appear to be any significant anthropometric or biochemical differences in this population (notably in 11oAs). Therefore, the PA and PP subgroups were treated as one case cohort (referred to in this study as the AAE group) for analysis of salivary microbiome measures.…”
Section: Methodsmentioning
confidence: 60%
See 1 more Smart Citation
“…Exclusion criteria were a history of chronic illness or other known endocrinopathies, evidence of adrenal enzyme defect, elevated inflammatory marker (C-reactive protein), history of hormone exposure, chronic glucocorticoid use, psychostimulant use, use of antibiotics in the prior 3 months, or use of probiotics in the last 1 month. The case group was previously subdivided into PA and PP subgroups based on elevation of adrenal androgen serum DHEAS in a prior study 4 ; however, as described in our publication, there did not appear to be any significant anthropometric or biochemical differences in this population (notably in 11oAs). Therefore, the PA and PP subgroups were treated as one case cohort (referred to in this study as the AAE group) for analysis of salivary microbiome measures.…”
Section: Methodsmentioning
confidence: 60%
“…Laboratory data usually reflect increased levels of DHEA, DHEAS, and androstenedione; recent studies have correlated 11-oxygenated 19-carbon steroids (11-oxygenated androgens [11oAs]) with the clinical signs of pubarche independent of adrenarche. 2 - 4 PA has been associated with obesity, metabolic syndrome, and polycystic ovary syndrome (PCOS), and may represent an early hyperandrogenic state in girls who later present with PCOS, with hyperinsulinism playing a key role. 5 - 9 …”
Section: Introductionmentioning
confidence: 99%
“…At the age of 3 years and 5 months, a serum 11-ketotestosterone (11KT) level was measured by commercial laboratory (Esoterix, Inc., Calabasas Hills, CA, USA) using liquid chromatography with tandem mass spectrometric detection (LC-MS/MS). 11KT was 26.3 ng/dL, which is elevated when compared to published data on a reference population of girls aged 4-5 years (range 7.3-10.9 ng/dL) and girls with premature adrenarche age 4-7 years (range 12.3-22.9 ng/dL) ( 17 ). The repeat 11KT at follow-up (chronological age 4 year 6 months) was still elevated at 33.8 ng/dL.…”
Section: Case Reportmentioning
confidence: 48%
“…Systematic longitudinal studies in children with WSS are warranted to address the apparent link between premature adrenarche, advanced bone age, and the pathophysiologic role of elevated 11KT, and to ensure reproducibility. We also acknowledge that the reference ranges for 11-oxygenated androgens in pediatric populations have been limited to two publications based on small sample sizes ( 17 , 18 ), and further studies are needed to validate age and sex-specific reference intervals. We do not have a DHEAS measurement in Case 1, however the DHEA concentration of Case 1 was normal.…”
Section: Discussionmentioning
confidence: 99%
“…As the biosynthesis of 11-oxygenated androgens depends on cytochrome P450 family 11 subfamily B member 1 (CYP11B1), an adrenal-specific enzyme, they should also be adrenal-specific [13]. It has been shown that 11-oxygenated androgens are elevated in adrenal-related androgen excess as congenital adrenal hyperplasia (CAH) or premature adrenarche and Cushing's disease [14,17,18]. In addition, they may also be elevated in some [19,20], but not all patients [21] with PCOS.…”
Section: Introductionmentioning
confidence: 99%